A reflection about research approach with emphasis in the qualitative-quantitative integration - Landim, Fátima Luna Pinheiro (2012)
This article aims to promote a reflection about the theoretical-methodological approaches, giving eminence to the qualitative-quantitative integration analysis in health research. It is emphasized, on one hand, the importance of each method, according to their characteristics, for sciences consolidation as a revelation tool of their specific objects. In counterpart, the authors invite us to a reflection about the subjacent integration of methods. For this purpose, they show differences between the ways of idealizing the research, suscitated by different reference charts to perceive and understand phenomenons, concluding with the consideration that, even different in relation to shape and emphasis, the qualitative and quantitative methods do not oppose each other, neither exclude each other, but they complement themselves with the purpose to reveal, in the most complete way as possible, the facets of a given phenomenon or social reality. Reflection in this field can help to clearly see the entails and the meaning of working with the integration of methods, in the actual context in which the knowledge production process needs to allow itself to transit between the disciplines, as a way of increasing its potential of intervention in society.